Women and feminized bodies facing facing energy inequality: experiences from the rural habitat - Huerta, Guadalupe (2024)
From a critical perspective, we ask ourselves what are the experiences of women and feminized bodies in the face of energy inequalities in the rural habitat of Pampa de Pocho (Córdoba, Argentina). Inequalities related to a civilizational crisis (Herrero, 2020; Teran Mantovani, 2020) on a global scale and with capital expansion processes through the advancement of the agribusiness frontier at the local level. For our analysis, we consider the experiences of those who are part of the Nuestra Granjas Unidas (NGU) community work group, with which we methodologically articulate participatory and situated devices for the co-construction of knowledge. These experiences are marked by unequal and limited access to the energy resources necessary for the sustainability of life. These difficulties imply the development of multiple daily strategies that intensify the time of those days that are responsible for the work of reproduction, which includes productive and reproductive tasks carried out in an interrelated way. In this context, community organization is a tool that facilitates the production, exchange and appropriation of knowledge, in addition to allowing the management of state resources through access to public policies that finance improvements in both living and working conditions.